2022
DOI: 10.1177/15344843221141515
|View full text |Cite
|
Sign up to set email alerts
|

Conducting and Writing a Structured Literature Review in Human Resource Development

Abstract: This article describes how to develop, conduct, and write a structured literature review (SLR) and cites examples of published SLR to illustrate different perspectives on the process and contributions to the literature. We first discuss how the SLR differs from other types of reviews (i.e., integrative literature review, meta-analysis, and scoping review). Second, the process of writing an SLR is discussed across common manuscript components: (1) the research problem, (2) conceptual or theoretical framework, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…To enhance existing knowledge from adjacent fields on humor use to coaching we used a Systematic Literature Review (SLR) methodology, PRISMA, and conducted our search based on their guidelines ( Moher et al, 2016 ). While our work follows the structure of a SLR, some aspects of this review lean more toward an Integrative Literature Review, as described by Rocco et al (2023) . For instance, our purpose was to use different literature streams to make meaning in the field of coaching, and in the presentation, we gave a coherent conceptual structuring of findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enhance existing knowledge from adjacent fields on humor use to coaching we used a Systematic Literature Review (SLR) methodology, PRISMA, and conducted our search based on their guidelines ( Moher et al, 2016 ). While our work follows the structure of a SLR, some aspects of this review lean more toward an Integrative Literature Review, as described by Rocco et al (2023) . For instance, our purpose was to use different literature streams to make meaning in the field of coaching, and in the presentation, we gave a coherent conceptual structuring of findings.…”
Section: Methodsmentioning
confidence: 99%
“…To minimize the risk of bias, we adhere to the review steps outlined by PRISMA ( Moher et al, 2016 ). Although our study has some characteristics of an Integrative Literature Review (ILR) like a more reflective analysis and some coherent conceptual structuring of the results, this article mostly follows the structured and detailed method of a SLR that can be replicated ( Rocco et al, 2023 ). This evidence-informed methodology minimizes the risk of results being inadequate or incomplete.…”
Section: Methodsmentioning
confidence: 99%
“…While much as written about the expectations for empirical data, such as trustworthiness, reliability, and validity, far less has been written about the quality characteristics of the supporting literature in academic writing. Guidelines on the academic genre of reviews of literature, such as structured, integrated, and scoping (Rocco et al, 2023), offer elaborate criteria on the boundaries of a given review as well as the treatment of a set of potential articles and other sources (for a good example of a careful treatment of the literature in a systematic review of literature, see Hauk & Gröschner, 2022). Outside of this genre, however, authors are left to their own devices when crafting a manuscript and are faced with a typically very large body of existing research on a given topic.…”
Section: Role and Function Of The Existing Literature In Academic Wri...mentioning
confidence: 99%
“…In our own domain, detailed guidance on the selection from the wider literature is equally sparce. In an otherwise highly instructive paper in this journal (Rocco et al, 2023), the authors reference a previous editor who observed "inconsistencies, weak descriptions of the search process, and confusion about different types of reviews" (p. 105). While Rocco and colleagues address reviews of literature as a specific genre of academic research, the task of selecting and representing existing literature sources is a critical part of all forms of academic writing.…”
mentioning
confidence: 99%